2021
DOI: 10.2147/cmar.s353233
|View full text |Cite
|
Sign up to set email alerts
|

The lncRNA HOXA11-AS Regulates Rab3D Expression by Sponging miR-125a-5p Promoting Metastasis of Osteosarcoma [Corrigendum]

Abstract: The authors have advised due to an error at the time of figure assembly, Figure 3B on page 4512 is incorrect. The correct Figure 3 is shown below.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Recent investigations showed that with the development of cervical cancer, the levels of miR-338-3p [5], miR-187 [6], and miR-433 [1] significantly decreased, but miR-221-3p expression upregulated [3]. Downregulation of miR-125a-5p had been revealed in colorectal cancer, gastric cancer, bladder cancer, and osteosarcoma [16,[41][42][43]. Our study found that miR-125a-5p levels also were downregulated in cervical cancer tissues, demonstrating that it could be connected with cervical cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Recent investigations showed that with the development of cervical cancer, the levels of miR-338-3p [5], miR-187 [6], and miR-433 [1] significantly decreased, but miR-221-3p expression upregulated [3]. Downregulation of miR-125a-5p had been revealed in colorectal cancer, gastric cancer, bladder cancer, and osteosarcoma [16,[41][42][43]. Our study found that miR-125a-5p levels also were downregulated in cervical cancer tissues, demonstrating that it could be connected with cervical cancer.…”
Section: Discussionmentioning
confidence: 99%